An approach for graphical user interface external bad smells detection - Silva, João Carlos (2014)
In the context of an effort to develop methodologies to support the evaluation of interactive system, this paper investigates an approach to detect graphical user interface external bad smells. Our approach consists in detecting user interface external bad smells through model-based reverse engineering from source code. Models are used to define which widgets are present in the interface, when can particular graphical user interface (GUI) events occur, under which conditions, which system actions are executed, and which GUI state is generated next. From these models we obtain metrics that can later be used to identify the smells.